Acute effects of inspiratory muscle warm-up on muscle oxygenation, perceived exertion and prefrontal cortical activation - Xinyu Dai; Jihong Yan; Xuecui Bi (PLoS ONE, 2025)
Objectives As rowing training loads intensify, the resulting high subjective exertion may force athletes to expand excessive neural impulses and cognitive resources. Given the finite nature of neural capacity, prolonged exposure to such demands could impair information processing, movement stability, and even causing non-contact injury. Therefore, this study aimed to investigate the effects of respiratory muscle warm-up intervention on prefrontal cortex and muscle oxygenation dynamics in athletes, thereby exploring its potential to mitigate cognitive-motor strain under rowing training conditions. Methods A total of 54 participants were recruited for the study, with an average age of 21.35 years. They were randomly assigned to one of three groups: Inspiratory muscles warm-up (IMW), placebo, or blank control. A portable muscle oximeter (Moxy, USA) was employed to monitor the muscle oxygen saturation level of the subjects throughout the training period. The degree of activation of the prefrontal cortex (PFC) was quantified by means of an oxygenation monitoring system (OctaMon). Concurrently, the CR10 scale was utilized to assess perceived exertion. Results Following the intervention, a significant difference in CR10 was observed between the various groups. A series of multiple comparisons demonstrated that the CR10 in the IMW group exhibited a significantly lower value than that observed in the placebo and control groups (p < 0.001). Once the baseline values from the pretest had been accounted for, a significant difference in oxygen saturation was observed between the different groups in the bilateral PFC. Post hoc analysis demonstrated significantly decreased HbO₂ in both the IMW (p = 0.019) and placebo (p = 0.035) groups relative to blank controls. Following the IMW intervention, the muscle oxygen saturation levels of the biceps brachii and vastus medialis in the subjects were significantly higher than those observed prior to training (p < 0.05). However, no significant difference was noted between the two tests in the control group, indicating that the IMW intervention can mitigate the decline in muscle oxygenation during training, alleviate discomfort in the lungs and motor muscles, and regulate subjective load. Conclusion The implementation of IMW intervention has the potential to mitigate the subjective burden experienced by athletes, thereby reducing discomfort during training. The combination of PFC activation level and muscle oxygen saturation index provides a superior explanation of the results. Nevertheless, further research is required to ascertain whether IMW can have a sustained positive impact.